PERANCANGAN ALAT PEMERAS MADU SYSTEM OTOMATIS DI KABUPATEN SUMBAWA - Pupung; Mietra Anggara; Vivin Nila Rakhmatullah (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2020)
Mead is a sweet and thick food containing gold to chocolate with high sugar content and low fat. But mead farmers have a mead squeeze process, because mead farmers in Sumbawa still use traditional methods. Related to this at the time of extortion and comfort of mead farmers. Furthermore, a mead squeezer machine is needed as a solution to improve the work process of mead farmers in producing quality mead water. The press from this automatic mead-squeezer produces mead water that is not mixed with the residue of the residual nest. This extortion process takes a short amount of time to squeeze meadcombs with a capacity of 3 kg in just 10 minutes. At this time meadcomb dregs are stuck to the walls of the filter and do not come mixed with mead water depending on the filter hole which is very small and neat. This extortion process uses an electric motor with a rotation of 1400 RPM as a drive or filter player that is transmitted by the van-belt.